The frequency of mutations in the penA, mtrR, gyrA and parC genes of Neisseria gonorrhoeae, the presence of tetM gene and antibiotic resistance/susceptibility: a systematic review and meta-analyses - Mendes, Ana Clara; de Souza, Renan Pedra; Bahia, Diana (Frontiers in Microbiology, 2025)
Gonorrhoea is currently one of the most important Sexually Transmitted Infections (STIs) due to the increased spread of multiresistant N. gonorrhoeae strains. The goal of this study was to analyse the relationship between resistance or decreased susceptibility to antibiotics in N. gonorrhoeae and the presence of mutations in the genes penA, mtrR, tetM, gyrA and parC. We conducted a systematic review following the PRISMA guidelines. We selected 19 studies for the penA gene, 23 for gyrA and parC, 18 for mtrR, and 12 for tetM using the Science Direct and PubMed databases. Meta-analyses of isolates resistant to penicillin, cefixime, and ceftriaxone showed that more than 50% of the isolates had mutations in the genes penA and mtrR. More than 50% of azithromycin-resistant isolates had mutations in the mtrR gene, while more than 50% of the isolates resistant and intermediate-resistant to ciprofloxacin had mutations in gyrA. Less than 50% of isolates with intermediate resistance to ciprofloxacin had mutations in parC. The plasmid containing the tetM gene was found in more than 50% of tetracycline-resistant isolates. Infection monitoring and genetic studies are important to control the spread, which can improve the quality of life of infected individuals and lessen the financial burden on public healthcare systems.